Estudo dos fatores de risco e prevalência de cervicite por Chlamydia trachomatis em adolescentes do município de Botucatu, São Paulo - Ferreira, Camila Paul [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Some characteristics and behaviors, that are of young, as a tendency to rebel and take risks, deviating from the rules of society, makes it vulnerable to many detrimental aspects, such as may indiscriminate use of alcohol and drugs, practicing unsafe sex and having multiple partners, which cause, among another complications, sexually transmitted diseases (STD). The Chlamydia trachomatis causes chlamydial infection, is one of the most recurrent STD of the world. Several risk factors are already defined for Chlamydial infection, among them, age under 25 years old and sexual behavior of the risk. The objective was to determine the prevalence of Chlamydia infection cervicitis in adolescent females of the Botucatu, São Paulo, and risk factors associated with this infection. It is cross-sectional study, of the populational basis, performed together the nineteen basic health units of the Botucatu, São Paulo. The data were obtained through clinical interviews and gynecological examination on samples collected for laboratory analysis. The research of C. trachomatis was performed by polymerase chain reaction (PCR). This report presents preliminary data, which represent 19% of the sample checked. Were interviewed 37 adolescents with a mean age of 17 years (between 15th and 19th years old), average of years studied of the 8,19, 40% of the families lived on less than a minimum wage by person and 24,3% dosen’t has ownership of the house where they live. Mean age of first sexual intercourse of 14 years (between 12th and 16th years old), 24,3% regularly used condoms, 5,4% had a premature birth and 8,1% reported abortion. 75,7% had any complaints in the gynecological exam, pain in lower abdomen, the most prevalent. The prevalence of vulvovaginitis or vaginal flora altered was 54,1%. The prevalence of infection by C. trachomatis was 58%. Presence content was associated infection chlamydial and age... (Complete abstract click electronic access below)

Certas características e comportamentos típicos dos adolescentes como tendência à rebeldia e a correr riscos e aversão às regras da sociedade o torna vulnerável a série de eventos como uso indiscriminado de álcool e drogas, prática de sexo sem proteção e multiplicidade de parceiros, que podem acarretar dentre outros comprometimentos, doenças sexualmente transmissíveis (DST). A Chlamydia trachomatis causadora da infecção clamidiana, é uma das DST mais recorrentes mundialmente. Diversos fatores de risco já estão definidos para a infecção clamidiana, dentre eles, idade inferior a 25 anos e comportamento sexual de risco. Objetivou-se determinar a prevalência de cervicite por infecção clamidiana em adolescentes do sexo feminino de Botucatu, São Paulo e fatores de risco associados a essa infecção. Trata-se de estudo de corte transversal, de base populacional realizado junto às dezenove unidades básicas de saúde do município de Botucatu-SP. Os dados foram obtidos por meio de entrevista clínica e exame ginecológico com coleta de amostras para análise laboratorial. A pesquisa de C. trachomatis foi realizada por Reação em Cadeia da Polimerase (PCR). Este relato apresenta dados parciais, os quais representam 19,0% da amostra calculada. Foram investigadas 37 adolescentes com idade media de 16,9 (±1,3), média de anos estudados de 8,2 (±1,6), 40,0% das famílias viviam com menos de um salário mínimo per capita e 24,3% não tinham a posse da casa. Idade media da coitarca foi de 14,3 (±1,2), 24,3% faziam uso consistente de preservativos e 5,4% e 8,1% tinham tido parto prematuro anterior e aborto anterior, respectivamente. 75,7% apresentaram alguma queixa ginecológica no momento do exame sendo dor em baixo ventre a mais prevalente. A prevalência de vulvovaginite ou flora vaginal alterada foi de 54,1%, sendo que a vaginose bacteriana (VB) foi a afecção mais... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem em saude publica; Chlamydia trachomatis; Doenças sexualmente transmissiveis